Countersluicing. (20th October 2019) - Hiraiwa, Ken; Kobayashi, Yoshiaki
Abstract: Sluicing deletes everything but a wh phrase. We document a novel phenomenon in Japanese, what we call countersluicing, in which everything but a wh phrase (and what follows it) survives deletion. Countersluicing lacks an overt wh phrase but nevertheless functions as a wh question. We propose that both countersluicing and sluicing have a cleft structure as their underlying structure. Countersluicing is derived from applying argument ellipsis to ForceP. This is exactly the opposite of what happens in sluicing in Japanese: argument ellipsis applies to a topicalized FinP. We provide several pieces of evidence for our analysis, involving multiple foci, connectivity effects, the clausemate condition, and island sensitivity.